CD26: A prognostic marker of acute lymphoblastic leukemia in children in the post remission induction phase - Mende, Atheer Awad; Yusof, Faridah; Mehdi, Wesen Adel; Zainulabdeen, Jwan Abdulmohsin (National Cancer Center, Korea., 2015)
Background: ALL is an irredeemable disease due to the resistance to treatment. There are several influences which are involved in such resistance to chemotherapy, including oxidative stress as a result of the generation of reactive oxygen species (ROS) and presence of hypodiploid cells. Cluster of differentiation 26 (CD26), also known as dipeptidyl peptidase-4, is a 110 kDa, multifunctional, membrane-bound glycoprotein. Aim and objectives: The aim of this study was to evaluate the clinical significance of serum CD26 in patients with acute lymphoblastic leukaemia patients in the post remission induction phase, as well as the relationship between CD26 activity and the oxidative stress status. Materials and Methods: CD26, total antioxidant status (TAS), total oxidant status (TOS), and oxidative stress index (OSI), in addition to activity of related enzymes myeloperoxidase, glutathiones- transferase and xanthine oxidase, were analysed in sixty children with acute lymphoblastic leukaemia in the post remission induction phase. Results: The study showed significant elevation in CD26, TOS and OSI levels in patients with acute lymphoblastic leukaemia in the post remission induction phase in comparison to healthy control samples. In contrast, myeloperoxidase, glutathione-s-transferase and xanthine oxidase activities were decreased significantly. A significant correlation between CD26 concentration and some oxidative stress parameters was evident in ALL patients. Conclusions: Serum levels of CD26 appear to be useful as a new biomarker of oxidative stress in children with acute lymphoblastic leukaemia in the post remission induction phase, and levels of antioxidants must be regularly estimated during the treatment of children with ALL.